Health Concerns among Sri Lankan Female Foreign Domestic Worker Returnees from the Middle East - Mun, Mirna Hodzic; De Silva, Janithra; de Oliveira, Justine Strand; De Silva, Vijitha; Malhotra, Rahul; Wijeratne, Monika; Tharindra, Hemajith; Østbye, Truls (Gestão e Sociedade, 2019)
Female foreign domestic workers (FDWs) are an important and growing occupational group, especially in the Middle East. Although Sri Lankan female FDWs comprise a significant percentage of those employed in this region, little is known about the health issues this population experiences during their employment. Prompted by this dearth in the extant literature, this study aimed to explore self-reported health problems and perceived causes, as well as health behaviors, beliefs, coping, and concerns of Sri Lankan female FDWs through the narratives of returnees formerly employed in the Middle East. Implementing a multi-faceted qualitative approach, focus group discussions and in-depth interviews were utilized to investigate FDWs’ health problems, behaviors, and coping mechanisms. Participants’ health beliefs and concerns were explored through free listing and pile sorting. Data was analyzed using thematic analysis and descriptive statistics. Headaches, backache, irregular meals and symptoms of depression were the most frequently self-reported health issues, most commonly attributed to overwork. Cleanliness was the most commonly adopted health maintaining behavior. The presence of cultural health beliefs in terms of illness causation was revealed, and FDWs’ spoke of the perceived health benefits of social interaction and religious practice as coping strategies. Findings of this study have several implications for policy and future research. FDWs’ concerns and recommendations prompt the need for greater accountability, legal enforcement of policies, and strengthened training and health monitoring. Policy, prevention and intervention measures may be more effective if they consider FDWs’ self-reported health problems, health belief models, health maintaining behaviors, concerns and coping strategies